Modulation and application of chitosal to adsorb lead (Pb2+) in waterwaste - TRAN THI HONG NGOC; PHAN TRUONG KHANH; NGUYEN VAN TUAN; K. PHILLIPS (Aerul şi Apa: Componente ale Mediului, 2017)
One of methods to eliminate metals from water is the use of adsorption. Chitosal is a material with a biological origin and was chosen for this study. The material was extracted from shrimp shells. The final product of the extraction progress was chitosal gel with a diameter of 3.5 mm, 97% of purity and good solubility in 1% CH3COOH solution. Three adsorption columns were built with PVC plastic. Two experiments at lead concentration 6.98 mg/l and 15.7 mg/l were carried out with the flow from the top down, at different water retention times of 15 minutes, 30 minutes, 45 minutes, 60 minutes, 90 minutes, and 120 minutes. The results showed that at lead concentrations of 6.98 mg/l we did not find the optimum water retention time. However, in the second experiment with lead concentration of 15.7 mg/l we determined the optimal water retention time was 60 minutes for column h1 and the lead adsorption efficiency achieved was 30.44%; column h2, h3 were the same time (90 minutes) and the lead adsorption efficiency reached 44.71%; and 52.87% respectively.